Estudo comparativo dos métodos coprológicos de Lutz, Kato-Katz e Faust modificado A comparative study of the coprologic methods of Lutz, Kato-Katz and the Faust modified - Adelú Chaves; Olinda Siqueira de Alcantara; Omar dos Santos Carvalho; José Soares dos Santos (Universidade de São Paulo, 1979)
Foram estudados, comparativamente, em 500 pacientes, os métodos de exames de fezes de Lutz, Faust modificado e Kato-Katz para o diagnóstico parasitológico de fezes. O método de Kato-Katz proporcionou maiores índices de positividade do que as outras duas técnicas no diagnóstico de ancilostomideos, T. trichiurus e S. mansoni. Nenhuma diferença foi observada quanto ao diagnóstico de A. lumbricoides. Para o diagnóstico das protozooses não houve diferença significativa entre os métodos de Faust modificado e de Lutz. Baseado nos dados obtidos, eficiência, simplicidade e rapidez de execução recomenda-se a associação dos métodos de Kato-Katz e Faust modificado na rotina de diagnóstico parasitológico de fezes. A comparative study was of the Lutz, Faust (modified), and Kato-Katz stool examination methods for parasitological diagnosis using 500 patients. The Kato-Katz method provided higher rates of positivity than the other two techniques in the diagnosis of Ancylostomidae, T. trichiurus, and S. mansoni. No differences were observed in the diagnosis of A. lumbicoides. Nor was a statistically significant difference observed in the diagnosis of protozoosis when using the Lutz and modified Faust methods. The data obtained led to a recommendation for an association of Kato-Katz and modified Faust methods for routine parasitological diagnosis due to Us simplicity, rapidity, and efficiency.